Dermatofibrosarcoma protuberans - an atypical tumor with a typical diagnostic dilemma: a case report - Kumar, Manoj; Gupta, Rohit; Kumar, Manoj; Jha, Ashesh (International Surgery Journal, 2023)
Dermatofibrosarcoma protuberans (DFSP) is a rare tumor of dermal fibroblast. Diagnosis poses a challenge to every surgeon. Its propensity to recur can be attributed to its characteristic finger-like projections, misdiagnosis, and incomplete excision. Wide local excision with adequate margins may lead to functional defects and cosmetic blemishes. Most cases undergoing second surgery warrants reconstructive procedure which might further complicate the management. We report a case of DFSP, initially misdiagnosed and underwent incomplete excision, later presented with recurrence and atypical features. High-grade suspicion is of paramount importance for ascertaining the diagnosis of DFSP and its appropriate treatment.